Telemonitoring and decision support system for covid-19 patients in the hospitalization area - Céspedes Ramos, Jhon Wildert (2020)
The coronavirus pandemic was identified as a new beta-corona-RNA virus that has now been called severe acute respiratory syndrome coronavirus 2 (SARS - CoV - 2), due to its similarity to SARS - CoV1. The World Health Organization (WHO) has declared the coronavirus disease 2019 (COVID - 19) as a pandemic due to the alarming levels of spread, severity and inaction, currently there are more than 5.2 million infections in the world, In Peru there are more than 115 thousand infected, this disease has had a strong impact on the health team: numerous infections were registered in health personnel, mainly in those who provide functions in the first line of care for suspected or confirmed cases. In this way, when there are high rates of contagion within the health team, health systems lose the ability to provide an appropriate response, reducing the resilience of the health system. In Peru there are more than a thousand infected doctors, one of the reasons is the constant interaction with infected and suspected patients, also the scarce personal protective equipment, and the late delivery to health personnel (PPE), for everything before aforementioned, a proposal is made for a telemonitoring and decision support system for covid-19 patients in the hospitalization area.